2022
DOI: 10.3390/ijms23052758
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell-Signaling Pathways by Berbamine in Different Cancers

Abstract: Natural product research is a cornerstone of the architectural framework of clinical medicine. Berbamine is a natural, potent, pharmacologically active biomolecule isolated from Berberis amurensis. Berbamine has been shown to modulate different oncogenic cell-signaling pathways in different cancers. In this review, we comprehensively analyze how berbamine modulates deregulated pathways (JAK/STAT, CAMKII/c-Myc) in various cancers. We systematically analyze how berbamine induces activation of the TGF/SMAD pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Berbamine is a bis-benzylisoquinoline alkaloid. It has been isolated from the traditional Chinese medicinal herb Berberis amurensis (37,38). Additionally, it has been identified in the tree turmeric plant (Berberis aristata), which is traditionally utilized in dietary and Ayurvedic practices for its anti-inflammatory and antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%
“…Berbamine is a bis-benzylisoquinoline alkaloid. It has been isolated from the traditional Chinese medicinal herb Berberis amurensis (37,38). Additionally, it has been identified in the tree turmeric plant (Berberis aristata), which is traditionally utilized in dietary and Ayurvedic practices for its anti-inflammatory and antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that Berbamine analogs were a novel anti-PEDV drug candidate. Berbamine is a bis-benzylisoquinoline alkaloid isolated from the traditional Chinese herb Berberis amurensis [ 14 ]. Berbamine inhibits various viruses, including SARS-CoV-2, MERS-CoV, JEV, ASFV, and EBOV [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Berbamine (BBM), Fangchinoline (FAN), and (+)-Fangchinoline (+FAN) are a few types of bis-benzylisoquinoline alkaloids that are extracted from natural medicinal plants [ 13 ]. These three compounds have various biological activities, including antiviral, anticancer, and anti-inflammatory activities, by modulating different cell-signaling pathways [ 14 , 15 , 16 ]. In a study of antiviral drugs, BBM was reported to inhibit Middle Respiratory Syndrome Coronavirus (MERS-CoV), Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), Japanese encephalitis Virus (JEV), Ebola virus (EBOV), and African Swine Fever Virus (ASFV) infections [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Berbamine (BBM), a bisbenzylisoquinoline alkaloid, is a natural, potent, pharmacologically active biomolecule isolated from the shrub Berberis amurensis . BBM modulates different cell-signaling pathways (JAK/STAT, CAMKII/c-Myc) in various cancers ( 3 ), is effective as an anti-diabetic supplement ( 4 ), and, more recently, was reported to inhibit the entry of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) virus, the causative agent of COVID-19, into host cells ( 5 ). However, there are few studies on how BBM regulates mycobacteria.…”
Section: Introductionmentioning
confidence: 99%